1967
DOI: 10.1017/s0022172400045903
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of staphylococcal infection and its prevention among infants and mothers after childbirth in hospital and at home

Abstract: Staphylococcal colonization and infection were studied prospectively in infants, mothers and households after childbirth at home and in hospital. Infants were treated prophylactically with frequent applications of ‘Ster-zac’ hexachlorophane dusting powder. Some were treated in addition with ‘Naseptin’ nasal disinfectant cream.The incidence of staphylococcal sepsis in infants was much less than before the adoption of hexachlorophane prophylaxis. The sepsis rate was further reduced when ‘Naseptin’ was used in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1968
1968
1986
1986

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Hence it seemed likely that hexachlorophane absorption through the skin was still less than that indicated by the blood analyses, with an even greater margin of safety. This would be consistent with the absence of reported damage to any of the many thousands of infants treated with 'Ster-Zac' powder, in many hospitals, since the method was introduced in Bristol about 18 years ago (Gillespie, Simpson & Tozer, 1958;Baber et al 1967).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Hence it seemed likely that hexachlorophane absorption through the skin was still less than that indicated by the blood analyses, with an even greater margin of safety. This would be consistent with the absence of reported damage to any of the many thousands of infants treated with 'Ster-Zac' powder, in many hospitals, since the method was introduced in Bristol about 18 years ago (Gillespie, Simpson & Tozer, 1958;Baber et al 1967).…”
Section: Introductionsupporting
confidence: 80%
“…that was found to be toxic when maintained in rats or monkeys for many weeks Hart, 1971). Hexachlorophane undoubtedly has prevented much staphylococcal sepsis in infants (Simpson, Tozer & Gillespie, 1960;Gluck & Wood, 1961;Pleuckhahn & Banks, 1963;Baber et al 1967). The incidence of breast abscess in mothers was also reduced (Corner, Crowther & Eades, 1960;Plueckhahn & Banks, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with Phisohex (3 % hexachlorophane in detergent cream), the established surgical scrub of the operating team for many years, Hibiscrub Introduction Since the first British report on Phisohex (Smylie et al, 1959), 3 % hexachlorophane detergent preparations have dominated the choice of safe and effective agents for the surgical scrub regimen. There is no doubt that both in this field (Lowbury et al, , 1963 and in others, notably infant care (Plueckhahn and Banks, 1963;Baber et al, 1967), the disinfectant hexachlorophane has been shown to contribute significantly to the control of hospital cross-infection. As a narrow spectrum agent acting mainly against skin cocci the continuous use of this compound has been criticized (Forfar et al, 1968) because it gives a selective encouragement to Gram-negative infections.…”
mentioning
confidence: 99%
“…frequently result (Gillespie et al 1958). In an attempt to control staphylococcal infection in infants, the effects of daily bathing with hexachlorophene have been studied (Baber et al 1967;Forfar et al 1968;Light et al 1968;Williams & Oliver 1969;Johnson et al 1976). In all these investigations significant reductions in rates of staphylococcal colonization and the subsequent development of infection have been demonstrated.…”
Section: Mixed Resultsmentioning
confidence: 99%